Architectural Heritage in Cinema and Digital Filmmaking: Digital Reconstruction, Accuracy, and Public Interpretation - Mouaki Benani, Moundher; Onescu, Iasmina (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2026)
This paper explores architectural heritage representation in cinema and digital filmmaking through fictional, documentary, and hybrid modes. Using digital visualization and narrative analysis, it examines digital reconstruction, computer-generated imagery CGI, accuracy, and audience understanding. Selected case studies show how cinematic heritage can attract audiences while requiring evidence to avoid historical and architectural distortion.
Keywords: Architectural Heritage; Cinematic Representations; Digital Reconstruction; Public Interpretation; Heritage Accuracy